Laboratory rotational spectroscopy of cyano substituted polycyclic aromatic hydrocarbons. Issue 4 (3rd March 2018) - McNaughton, Don; Jahn, Michaela K; Travers, Michael J; Wachsmuth, Dennis; Godfrey, Peter D; Grabow, Jens-Uwe
Abstract: The rotational spectra of the four cyano substituted polycyclic aromatic hydrocarbon (PAH) molecules 1-cyanonaphthalene, 2-cyanonaphthalene, 9-cyanoanthracene, and 9-cyanophenanthrene have been recorded in molecular expansions using a Stark-modulated millimetre-wave spectrometer and a Fourier transform microwave spectrometer in the centimetre-wave region. The spectra have been assigned and fitted to provide molecular constants and quadrupole hyperfine constants of sufficient accuracy to enable complete hyperfine structure line predictions for interstellar searches. The data may provide a route into detection of small PAHs in the interstellar medium.